UNEMPLOYMENT IN NIGERIA: LESSONS OF THE GREAT DEPRESSION (1929-35) AND THE FINANCIAL MELTDOWN (2008-09) IN WESTERN EUROPE AND THIRD WORLD COUNTRIES (Singaporean Journal of Business Economics and Management, 2014)
This paper analyzed the factors that may be attributable to the high level of unemployment, over the years in Nigeria and other notable third world countries (TWCs) and the ways to reverse the trend in this 21st century. Nigeria's vision 20:2020 sets the target of the nation becoming one of the 1 twenty (20) buoyant economies in the world. Nigeria was lowly rated in terms of economic development (currently at about 89th position by the United Nations Development Program [UNDP] Report 2010). This paper identified the absence of appropriate legal regime, political and economic policies inconsistency; power-pool crises, urban explosion and so on, as the major constraints and development obstacles to achieving industrialization and the attendant jobs creation in Nigeria. This paper argued that padegogic commitment by leadership at all levels in TWCs was imperative for gainful employment creation through manpower development in critical skills. More so, the abandonment of the rural agrarian economy over the years have precipitated rural-urban disparity in development and migration, rising rural vicious-cycle of poverty, urban food insecurity, with its negative social consequences of low-savings and investment and the general trend in various types of joblessness in the TWCs, to which Nigeria was not insulated. The lessons to be learnt in Nigeria to achieve massive jobs creation include: the FGN immediate institutional reforms to revamp the moribund key industries, the overhaul of poorly managed and distressed banking sector with re-capitalization and merger schemes, sinking fund into agriculture and the power sector to achieve sustainable jobs creation as was done in the United States by President Franklin Roosevelt in 1933 and Barack Obama in 2009.